Synthesis, in vitro bioassays, and computational study of heteroaryl nitazoxanide analogs - Tasmia Ahmed; S. M. Abdur Rahman; Muhammad Asaduzzaman; Abul Bashar Mir Md. Khademul Islam; A. K. Azad Chowdhury (Wiley, 2021)
Abstract Antiprotozoal drug nitazoxanide (NTZ) has shown diverse pharmacological properties and has appeared in several clinical trials. Herein we present the synthesis, characterization, in vitro biological investigation, and in silico study of four hetero aryl amide analogs of NTZ. Among the synthesized molecules, compound 2 and compound 4 exhibited promising antibacterial activity against Escherichia coli (E. coli), superior to that displayed by the parent drug nitazoxanide as revealed from the in vitro antibacterial assay. Compound 2 displayed zone of inhibition of 20 mm, twice as large as the parent drug NTZ (10 mm) in their least concentration (12.5 µg/ml). Compound 1 also showed antibacterial effect similar to that of nitazoxanide. The analogs were also tested for in vitro cytotoxic activity by employing cell counting kit‐8 (CCK‐8) assay technique in HeLa cell line, and compound 2 was identified as a potential anticancer agent having IC50 value of 172 µg which proves it to be more potent than nitazoxanide (IC50 = 428 µg). Furthermore, the compounds were subjected to molecular docking study against various bacterial and cancer signaling proteins. The in vitro test results corroborated with the in silico docking study as compound 2 and compound 4 had comparatively stronger binding affinity against the proteins and showed a higher docking score than nitazoxanide toward human mitogen‐activated protein kinase (MAPK9) and fatty acid biosynthesis enzyme (FabH) of E. coli. Moreover, the docking study demonstrated dihydrofolate reductase (DHFR) and thymidylate synthase (TS) as probable new targets for nitazoxanide and its synthetic analogs. Overall, the study suggests that nitazoxanide and its analogs can be a potential lead compound in the drug development.